Rethinking Watercolor Pedagogy in Undergraduate Art Education: Current Challenges and Strategic Responses - Sun, Yingze (Education Insights, 2026)
Watercolor occupies a distinctive position in undergraduate art education due to its material sensitivity, technical complexity, and capacity for individual expression. Unlike other media, watercolor requires prompt judgment in managing water, pigment, and timing. Although Chinese undergraduate institutions have accumulated substantial teaching experience, classroom practice often remains dominated by teacher-centered demonstration and imitation. Consequently, while students achieve technical stability, their creative confidence, aesthetic judgment, and adaptive professional competence remain underdeveloped. In response to diversified artistic practices and higher expectations for innovative talent, conventional watercolor pedagogy requires urgent reconsideration. This paper revisits undergraduate watercolor teaching through the lenses of educational purpose, curriculum structure, classroom methodology, and student development. It outlines the medium-specific characteristics demanding a responsive teaching model and reviews existing scholarship, noting a prevalent focus on technical foundations. The study analyzes major challenges in current education, including outdated instruction, excessive technical drills at the expense of originality, inadequate aesthetic cultivation, and weak connections to professional practice. To address these issues, the paper proposes practical strategies: student-centered pedagogy, layered curriculum design, critical appreciation training, digital resource integration, expanded field practice, and multidimensional assessment. Ultimately, watercolor teaching must transcend narrow technical transmission to cultivate students’ abilities to observe, interpret, experiment, and create. Balancing foundational training with innovation and real-world engagement is essential to foster independent, perceptive, and creative art graduates.